Auto-reactivity against gut bacterial peptides in patients with late-onset diabetes. (2nd October 2020) - Sajid, Mohammad; Biswas, Krishna; Singh, Harpreet; Negi, Sapna
Abstract: The depletion of gut mucosal barrier enables exposure of gut microbes/gut microbial products to the host mucosal immunity which may increase the risk of metabolic/inflammatory disorders. These immune responses can lead to the development of mild autoimmunity to metabolic peptides coming from gut bacteria and may result in metabolic diseases like late-onset diabetes (LOD). In the present study, we identified host sera cross-reactivity with gut bacterial peptides similar to host proteins. The interaction between diabetic sera and gut peptides was detected by enzyme-linked immunosorbent assay (ELISA) and results were confirmed using surface plasmon resonance (SPR). The ELISA assay showed a higher level of serum cross-reactivity in LOD patients as compared to non-diabetic controls against three peptides (P-5, P-9, and P-13). SPR analysis confirmed binding-affinity against P-5 and P-13. Also, a significant correlation was observed between inflammatory markers and P-5. This study demonstrates that gut health is important not only for intestinal diseases but also for several late-onset diseases, like, diabetes.